Analysis of Some Binary Transition Metal Ion Mixtures Using Iron(II) as a Reductant in Phosphoric Acid Medium - VIJAYA RAJU, K.; BENARJI PATRUDU, T. (Asian Journal of Chemistry, 2010)
Simple, accurate and convenient titrimetric methods have been doveloped for the analysis of some synthetic binary transition metal ion mixtures [Ce(IV) + Mo(VI); Cr(VI) + Mo(VI); V(V) + Mo(VI); V(V) +V(IV); V(V) + Ce(IV) and V(V) + Cr(VI)] using iron(II) as a reductant in phosphoric acid medium. The method consists in titrating a metal ion mixture with iron(II) first in 6-7 M phosphoric acid medium using N-phenyl anthranilic acid (NPA) or ferroin as a redox indicator for Ce(IV), Cr(VI) or V(V) and then in 11-12 M phosphoric acid medium using resorufin as an indicator for Mo(VI) and V(VI). From the two titer values the amounts of metal ions present in mixtures can be computed. To explain the suitability of the redox indicators in the titrations, present workers have measured their transition potentials of the indicators used and compared them with the redox potentials of the metal ion systems.